Discordance between histologic and visual assessment of tissue viability in excised burn wound tissue. Issue 2 (26th December 2018) - Karim, Aos S.; Yan, Amy; Ocotl, Edgar; Bennett, Daniel D.; Wang, Ziyue; Kendziorski, Christina; Gibson, Angela L.F.
ABSTRACT: The regenerative capacity of burn wounds, and the need for surgical intervention, depends on wound depth. Clinical visual assessment is considered the gold standard for burn depth assessment but it remains a subjective and inaccurate method for tissue evaluation. The purpose of this study was to compare visual assessment with microscopic and molecular techniques for human burn depth determination, and illustrate differences in the evaluation of tissue for potential regenerative capacity. Using intraoperative visual assessment, patients were identified as having deep partial thickness or full thickness burn wounds. Tangential excisions of burn tissue were processed with hematoxylin and eosin to visualize tissue morphology, lactate dehydrogenase assay to ascertain cellular viability, and Keratin‐15 and Ki67 to identify epidermal progenitor cells and proliferative capacity, respectively. RNA from deep partial and full thickness burn tissue as well as normal tissue controls were submitted for RNA sequencing. Lactate dehydrogenase, Keratin‐15, and Ki67 were found throughout the excised burn wound tissue in both deep partial thickness burn tissues and in the second tangential excision of full thickness burn tissues. RNA sequencing demonstrated regenerative capacity in both deep partial and full thickness burn tissue, however a greater capacity for regeneration was present in deep partial thickness compared with full thickness burn tissues. In this study, we highlight the discordance that exists between the intraoperative clinical identification of burn injury depth, and microscopic and molecular determination of viability and regenerative capacity. Current methods utilizing visual assessment for depth of injury are imprecise, and can lead to removal of viable tissue. Additionally, hematoxylin and eosin microscopic analysis should not be used as the sole method in research or clinical determination of depth, as there are no differences in staining between viable and nonviable tissue.